Vaccine strategies against Babesia bovis based on prime-boost immunizations in mice with modified vaccinia Ankara vector and recombinant proteins - Jaramillo Ortiz, José Manuel (2014)
In this study, a recombinant modified vaccinia virus Ankara vector expressing a chimeric multi-antigenwas obtained and evaluated as a candidate vaccine in homologous and heterologous prime-boost immu-nizations with a recombinant protein cocktail. The chimeric multi-antigen comprises immunodominantB and T cell regions of three Babesia bovis proteins. Humoral and cellular immune responses were eval-uated in mice to compare the immunogenicity induced by different immunization schemes. The bestvaccination scheme was achieved with a prime of protein cocktail and a boost with the recombinantvirus. This scheme induced high level of specific IgG antibodies and secreted IFN and a high degree ofactivation of IFN+CD4+and CD8+specific T cells. This is the first report in which a novel vaccine can-didate was constructed based on a rationally designed multi-antigen and evaluated in a prime-boostregime, optimizing the immune response necessary for protection against bovine babesiosis.